2SPD-025 Optimising of planned drugs orders and reception platform activity. (March 2019) - Etienne, P; Vasseur, M; Depernet, S; Vitale, G; Beaugrand, N; Desplechain, M
Abstract : Background: In the establishment, the most commonly used medications are ordered according to a schedule, which is set up for the year. Purpose: The goal of this study is to quantify drug order amount per timetable in order to better dispatch future orders and, thus, reception activity (RA). This is to avoid drug shortages. Material and methods: The first part analysed retrospectively the RA from January to July 2018. Statistics on numbers of received lines per week were conducted, including only scheduled drugs. Discussions with the reception team were also held to evaluate pallet's volume of the different suppliers. In the second part, analysis of a future timetable has been made by extracting data from Copilote to process it with Excel. By taking into account the suggestions of the team and heterogeneity of RA, a new timetable with a new scheduling of suppliers was realised so as to have a reproducible activity independent from the day of reception. Results: Of 1873 referenced drugs, 86% have a scheduled ordering. On average, 390 lines of scheduled drugs (LSD) are received per week, with a 95% confidence interval (CI) of 363 to 418: these are important fluctuations. The field team also identified 17 suppliers as difficult to receive because of their pallet's size and number of different references per pallet. Taking these constraints into account, we succeeded in spreading them over time to have a reproducible pattern. The previous timetable had a mean of 260 LSD per calendar (CI: 246 to 275). Once reworked, the mean stayed the same, but the CI was 254 to 264, resulting in a better partition of the different suppliers. Conclusion: Nowadays, drug procurement is becoming challenging because of the number of drug shortages that hospitals have to face. This study reveals the necessity of better scheduling the planned drug orders, to optimise their reception. It is also necessary to re-evaluate these timetables as each drug market changes, in order to not disrupt the reproducible RA implemented here. References and/or acknowledgements: Petersen PE. World Health Organization. Organisation Mondiale de la Sante. Comm Dent Oral Epidemiol 2003;31:471–471. Ombaka E. Current status of medicines procurement. Am J Health Syst Pharm 2009;66:s20–s28. No conflict of interest.